2006
DOI: 10.1007/s00213-006-0611-0
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy of dopamine D1, D2 and serotonin2A receptors in schizophrenic patients treated with flupentixol in comparison with risperidone and haloperidol

Abstract: We were able to demonstrate a moderate 5-HT(2A) and D(1) occupancy under clinically relevant doses of flupentixol, albeit lower than expected from in vitro data and clearly below saturation. Therefore, if flupentixol's efficacy on negative symptoms is based on its interaction with 5-HT(2A) and/or D(1) receptors, it should be highly dependent on serum concentration and thus on dosage and metabolism. However, these data suggest that mechanisms other than D(1) or 5-HT(2A) antagonism may contribute to flupentixol'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…We are unable, therefore, to draw conclusions regarding the sub-type of DA receptors mediating the observed effects. Furthermore, as flupentixol is also known to bind with high affinity to other receptors, including serotonin (2A) and adrenergic (a1) receptors (Reimold et al, 2007;Testa et al, 1989) we cannot rule out the possibility that antagonism of these other neurotransmitter systems contributes to the behavioral effects of flupentixol reported here and elsewhere.…”
Section: Discussionmentioning
confidence: 77%
“…We are unable, therefore, to draw conclusions regarding the sub-type of DA receptors mediating the observed effects. Furthermore, as flupentixol is also known to bind with high affinity to other receptors, including serotonin (2A) and adrenergic (a1) receptors (Reimold et al, 2007;Testa et al, 1989) we cannot rule out the possibility that antagonism of these other neurotransmitter systems contributes to the behavioral effects of flupentixol reported here and elsewhere.…”
Section: Discussionmentioning
confidence: 77%
“…An analysis of three-dimensional structures and molecular electrostatic potentials confirms the higher receptor affinities of cis-flupentixol in comparison to the trans-isomer (Sylte and Dahl 1991). In the already mentioned PET study with flupentixol, the presented drug plasma concentrations appear to be those of the sum of cis-and trans-flupentixol, as the standard analytical technique used by MDS Pharma Services (Fehraltorf, Switzerland) was not developed for the separation of these isomers (Reimold et al 2007; and Petra Struwe, Celerion, Fehraltdorf, personal communication).Recently, the AGNP-TDM group (Arbeitsgemeinschaft für Neuropsychopharmakologie und Pharmakopsychiatrie) ) recommended published updated consensus guidelines for therapeutic drug monitoring in psychiatry: The therapeutic reference range (recommended plasma drug concentration) for the antipsychotic drug flupentixol (flupenthixol) was given as 1-10 ng/ml. This range is related to the sum of the cis-and the trans-isomers concentrations, and the recommended range is mainly based on 2 studies (Reimold et al 2007;Balant-Gorgia et al 1985).…”
mentioning
confidence: 99%
“…Such studies have been carried out for many antipsychotics, the binding of which to central dopamine D2 receptors can be observed with PET (Grunder et al 2011). A study showed a 50-70 % D2-receptor occupancy by therapeutic doses (4-10 mg/day; 5.7±1.4 mg/day [mean ± SD]) of the antipsychotic drug flupentixol, which reportedly lead to flupentixol plasma concentrations between 0 and 6 ng/ml (1.47±0.97 ng/ml) after oral administration of this drug to 13 patients (Reimold et al 2007). Flupentixol is available as a 1:1 mixture of the geometric isomers cis-and trans-isomers (Z-and E-isomers, respectively) for oral administration, while the depot preparation flupentixol decanoate contains only cis-flupentixol.…”
mentioning
confidence: 99%
See 2 more Smart Citations